Insights into the Localization and Function of the Membrane Trafficking Regulator GNOM ARF-GEF at the Golgi Apparatus in Arabidopsis . Issue 7 (10th July 2014) - Naramoto, Satoshi; Otegui, Marisa S.; Kutsuna, Natsumaro; de Rycke, Riet; Dainobu, Tomoko; Karampelias, Michael; Fujimoto, Masaru; Feraru, Elena; Miki, Daisuke; Fukuda, Hiroo; Nakano, Akihiko; Friml, Jiří
Abstract : This work presents a model of the plant intracellular trafficking system developed by analyzing the subcellular localization of GNOM ARF-GEF, which is crucial for auxin transport-mediated plant development. The data show that GNOM is associated with Golgi body, rather than endosomes as previously believed, and redefine our notions about the identity and function of recycling endosomes in plants. Abstract: GNOM is one of the most characterized membrane trafficking regulators in plants, with crucial roles in development. GNOM encodes an ARF-guanine nucleotide exchange factor (ARF-GEF) that activates small GTPases of the ARF (ADP ribosylation factor) class to mediate vesicle budding at endomembranes. The crucial role of GNOM in recycling of PIN auxin transporters and other proteins to the plasma membrane was identified in studies using the ARF-GEF inhibitor brefeldin A (BFA ). GNOM, the most prominent regulator of recycling in plants, has been proposed to act and localize at so far elusive recycling endosomes. Here, we report the GNOM localization in context of its cellular function in Arabidopsis thaliana . State-of-the-art imaging, pharmacological interference, and ultrastructure analysis show that GNOM predominantly localizes to Golgi apparatus. Super-resolution confocal live imaging microscopy identified GNOM and its closest homolog GNOM-like 1 at distinct subdomains on Golgi cisternae. Short-term BFA treatment stabilizes GNOM at the Golgi apparatus, whereas prolonged exposures results in GNOM translocation to trans -Golgi network (TGN )/early endosomes (EEs ). Malformed TGN /EE in gnom mutants suggests a role for GNOM in maintaining TGN /EE function. Our results redefine the subcellular action of GNOM and reevaluate the identity and function of recycling endosomes in plants.